Tracking Europe's water footprint, identifying potential economic vulnerability. (Research'eu results magazine)
Climate change is increasing water scarcity around the world and the interdependencies of global trade mean that the impact could ripple far and wide, including across Europe, as the EU-funded project IMPREX warns.